1976
DOI: 10.1115/1.3450613
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Radiating Fin Arrays With Respect to Weight

Abstract: A nonlinear optimization approach is used to determine the minimum weight design for radiating fin arrays used in space applications. Straight and circular fins of rectangular and triangular profile are considered for emissivities in the range of 0.8 to 1.0. The heat transfer analysis includes fin to fin and fin to base radiative interactions. The results, presented in graphical form, give the optimum geometries for the profiles considered in terms of dimensionless parameters. Thus, for specified values of hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1977
1977
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The integration constants C 1 and C 2 determined using the boundary conditions are given by equations ( 10) and (11) and substituted into equation (25). After some mathematical manipulations, the temperature distribution is obtained as…”
Section: Variation Of Parameters Methods For Nonlinear Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The integration constants C 1 and C 2 determined using the boundary conditions are given by equations ( 10) and (11) and substituted into equation (25). After some mathematical manipulations, the temperature distribution is obtained as…”
Section: Variation Of Parameters Methods For Nonlinear Problemsmentioning
confidence: 99%
“…It was considered as mutual irradiation and was observed that this had an important overall effect on the overall heat exchange process. Schnurr et al 11 used a nonlinear optimization approach to determine the minimum mass design for radiating finned arrays used in space. It was explained with two numerical examples that for specified values of heat transfer rate, base cylinder surface temperature, and thermal properties of fin material, minimum weight can be used to design fin arrays.…”
Section: Introductionmentioning
confidence: 99%
“…It was also noted that the radiation heat transfer is proportional to the cube root of the thermal conductivity to density ratio. Schnurr et al [16] similarly compared the effects of tapering circular fins along an annular heat pipe and found that increases in performance could be achieved. A minimum mass design for longitudinal fins extending from a flat base or cylinder was investigated by Chung and Zhang [17,18].…”
Section: Introductionmentioning
confidence: 95%
“…Besides, Love and Francis [5] analyzed longitudinal radiating fins equally spaced around a cylindrical heat source, while Eslinger and Chung [6] presented a finite element solution for the heat transfer from a radiating and convecting fin or fin arrays. Schnurr et al [7] optimized the radiating fin arrays with respect to weight. Here, a non linear optimization approach was used to determine the minimum weight design for radiating fin arrays used in space applications and the analysis were brought out.…”
Section: Introductionmentioning
confidence: 99%